Evidence That Microorganisms at the Animal-Water Interface Drive Sea Star Wasting Disease - Aquino, Citlalli A.; Besemer, Ryan M.; DeRito, Christopher M.; Kocian, Jan; Porter, Ian R.; Raimondi, Peter T.; Rede, Jordan E.; Schiebelhut, Lauren M.; Sparks, Jed P.; Wares, John P.; Hewson, Ian (Frontiers in Microbiology, 2021)
Sea star wasting (SSW) disease describes a condition affecting asteroids that resulted in significant Northeastern Pacific population decline following a mass mortality event in 2013. The etiology of SSW is unresolved. We hypothesized that SSW is a sequela of microbial organic matter remineralization near respiratory surfaces, one consequence of which may be limited O2 availability at the animal-water interface. Microbial assemblages inhabiting tissues and at the asteroid-water interface bore signatures of copiotroph proliferation before SSW onset, followed by the appearance of putatively facultative and strictly anaerobic taxa at the time of lesion genesis and as animals died. SSW lesions were induced in Pisaster ochraceus by enrichment with a variety of organic matter (OM) sources. These results together illustrate that depleted O2 conditions at the animal-water interface may be established by heterotrophic microbial activity in response to organic matter loading. SSW was also induced by modestly (~ 39%) depleted O2 conditions in aquaria, suggesting that small perturbations in dissolved O2 may exacerbate the condition. SSW susceptibility between species was significantly and positively correlated with surface rugosity, a key determinant of diffusive boundary layer thickness. Tissues of SSW-affected individuals collected in 2013 – 2014 bore δ15N signatures reflecting anaerobic processes, which suggests that this phenomenon may have affected asteroids during mass mortality at the time. The impacts of enhanced microbial activity and subsequent O2 diffusion limitation may be more pronounced under higher temperatures due to lower O2 solubility, in more rugose asteroid species due to restricted hydrodynamic flow, and in larger specimens due to their lower surface area to volume ratios which affects diffusive respiratory potential.